(untitled) - Phetole Mangena; Hitesh Dalvadi; Mahmoud Bahmani (Plant Biotechnology Persa, 2021)
Due to different cultures and areas for the use of medicinal plants, there are various customs and traditional valuable methods that botany offers for finding new medicinal plants and herbal medicines. Lack of useful and effective drugs for itching and skin inflammation leads to the expansion of research on effective and natural remedies for patients. For this systematic review, databases such as Web of Science, PubMed, PubMed Central, Scopus, SID, Magiran, and Google Scholar were used to have an access to articles on skin pruritus as well as the role of herbs in treating pruritus without release time limit. Words that were used separately in the title to retrieve articles as keywords included herbs, traditional medicine, herbal medicine, and itching. This article lists 19 plant species that are used in different parts of Iran as anti-pruritic herbal remedies. According to traditional Iranian ethnobotanical sources, Carthamus oxyacantha, Castor, Fumaria officinalis, Ziziphus, Milkvetch, Gallium verum, Trifolium repens, Fumaria asepala Boiss, Rumex chalepensis Mill, Salix elbursensis Boiss, Solanum nigrum, Chris, Verbascar citrulluscolocynthis, Matricaria recutita, Falcaria vulgaris Bernh and Anagallis arvensis are the most important medicinal plants used in Iranian ethnobotanical sources to treat pruritus. The researchers of the present study believe that the identification of antipruritic herbs is of great importance.